Analysis of sensitization profile in medium chromium ferritic stainless steel (FSS) welds - Amuda, Muhammed Olawale Hakeem; Mridha, Shahjahan (Universiti Tun Hussein Onn Malaysia, 2011)
The sensitization features in Ferritic Stainless Steel (FSS) welds are discussed in the present work. The welds were produced on a 1.5mm thick plate of 16wt%Cr FSS conforming to AISI 430 commercial grade, using TIG torch in argon environment at a heat flux between 1008W and 1584W and speed between 2.5mm/s and 3.5mm/s. The sensitization was evaluated by electrolytic etching of the weld cross sections in 10% oxalic acid. The characterization of the weld section for sensitization indicates that the size of the sensitized zone increases in direct proportion to the quantum of the heat input (combination of heat flux and welding speed). Microstructural analysis suggests that sensitization is promoted in the welds when the processing conditions (heat flux and welding speed) restricts the transformation occurring during cooling through the dual phase region, i.e. the welding conditions that promote transformation of delta ferrite (δ) to austenite (γ) during cooling cycle can prevent sensitization in the FSS welds and such conditions found in this investigation correspond to welding with a heat flux in the range 1008W to 1296W and speed 3mm/s to 3.5mm/s. These conditions of heat fluxes and welding speeds correspond to heat inputs in the range 288-432J/mm